Echa norwidowskie w polskich czasopismach emigracyjnych na Wyspach Brytyjskich w czasie i po drugiej wojnie światowej - Chwastyk-Kowalczyk, Jolanta (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
Poles who stayed in Great Britain during and after World War II, as well as those who came to the United Kingdom in the following emigration waves, brought with them the baggage of their own culture, national heroes, and ethos. An important figure in this context was Cyprian Norwid who was a true European, a citizen of the world, and at the same time a great patriot, poet, prose writer, playwright, essayist, graphic artist, sculptor, painter, philosopher, and highly regarded as the last of the four most important Polish Romantic poets. Remembrances of him and references to his work are usually intended to raise the spirit of the Polish nation and raise foreign awareness about his work in other cultural societies. Norwid is present in various Polish emigre presses that are edited in the Great Brittan. Traces of work can be found in many publications: Dziennik Polski (The Polish Daily), Dziennik Polski and Dziennik Żołnierza (The Polish Daily and Soldier’s Daily), Pamiętnik Literacki (Literary Diary). Surprisingly, Norwid did not appear in the following post-accession periodicals aimed at the intelligentsia: Nowy Czas (The New Time) or Ekspresje (Expressions). Norwid was important to the authors of Merkuriusz (Mercurius) and Nowy Merkuriusz-Kontynenty (New Mercurius - Continents), and these authors were Adam Czerniawski, Bogdan Czaykowski, Marian Czuchnowski, Wojciech Gniatczyński, Mieczysław Paszkiewicz, Florian Śmieja, and Bolesław Taborski. These writers appreciated his poetry more than the poetics of Skamander.